Trust Issues in the Health Communication of Childreen in Street Situation - Erwin Rasyid; Ade Putranto Prasetyo Wijiharto Tunggali; Hari Akbar Sugiantoro (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
Children in street situations are a social problem faced in various cities in Indonesia. Efforts to protect children in street situations facing multiple issues. One of them is related to fulfilling the identity rights of children in street situations. This study aims to identify how a communication approach can foster interpersonal trust in children on the streets. The type of research used is descriptive qualitative using a phenomenology approach. There are many problems affecting confidence in children in street situations. It started from a lack of security and health issues that were not touched upon to the communication approach's problem. Communication intensity is the primary key to gaining interpersonal trust from children in street situations. Children's communication patterns in unique street situations also need to be responded to with a more informal approach. The actors involved need to reconsider the type of empowerment shown to children in street situations.